Community-Based Waste Management Strategy in Nagari Pungguang Kasiak Through Waste Bank Innovation - Awalina, Rahmi; Putra, Haznam; Ayu Lestari, Resti (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2024)
A paradigm shift in waste management needs to be carried out in a sustainable manner. Education regarding residents' awareness and skills in applying the principles of reduce, reuse, recycle, and replant (4R) is very important to deal with waste problems from the source. Waste banks that involve women's participation serve as social capital in community-based management. In Nagari Pungguang Kasiak, Padang Pariaman Regency, Indonesia, a waste bank is implemented by integrating the 4R principles through the collection and sorting of dry waste, managed with a banking-like system, where what is saved is waste, not money. Community empowerment is carried out through counseling, education, and training with emancipatory participation methods, as well as interactive dialog within the community. In addition, building partnerships and cooperation mechanisms between waste bank managers and stakeholders is very important. The Sehati Waste Bank in Nagari Pungguang Kasiak has provided tangible benefits to the community, such as reducing waste volume, improving environmental cleanliness, and increasing economic independence. The economic benefits obtained from waste savings also contribute to electricity payments and food purchases. This program plays a role in creating a cleaner, greener, and healthier environment. With integrated waste management, community creativity and innovation can be encouraged, thereby improving the overall welfare of residents.